The Impact of Foreign Direct Investment, Economic Growth, Trade, and Covid-19 on Unemployment: Evidences from MENA - Azhar, Neng Zulfa (Muslim Business and Economics Review, 2023)
The objective of this study is to investigate the influence of foreign direct investment, economic growth, international trade, Covid-19 pandemic on unemployment rates in six developing Middle Eastern and North African (MENA) countries, as well as members of the Organization of Islamic Cooperation (OIC), over period 2010 to 2021. Quantitative approaches using panel regression fixed effect model are utilized. According to the findings of this study, all of the variable used include foreign direct investment, economic growth, international trade and the Covid-19 pandemic simultaneously have a substantial impact on unemployment rate in six MENA countries. While partially, foreign direct investment, economic growth and international trade have a strong influence in declining unemployment in six MENA countries, while the Covid-19 pandemic variable has a positive relation and insignificant effect on the unemployment rate which indicates that statistically there is no significant difference of the unemployment rate in the years before and during Covid-19 pandemic. In conclusion, since the MENA countries has experienced a high concentration of unemployment particularly among youth for a long time, the government ought to concentrate more on facilitating skills training support for young people. This will ensure that the young people have added value and are qualified in the sectors and fields offered, particularly in foreign direct investment, allowing the FDI to absorb domestic workers. The youth can so, collectively, escape unemployment and enhance productivity in a country, which will also raise the GDP of the country